Analyzing Risk Management in the Crystal Guava Agroindustry Supply Chain - Ni Kadek Pingkan Wulandari; A.A.A. Wulandira Sawitri Djelantik; I Made Sudarma; Ary Bakhtiar (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2025)
PT Kreasi Tani Bumiaji is an agro-industry enterprise located in the Bumiaji District of Batu City, dedicated to the production of crystal guava. The uncertainty of raw materials and marketing is the most significant challenge that PT Kreasi Tani Bumiaji encounters in its supply chain. At the conclusion of the season, crystal guava is exceedingly challenging to acquire, and the demand cannot be satisfactorily satisfied. Limited market share has prevented the company from optimizing production following the conclusion of the harvest season. This research endeavors to ascertain the structure and mechanism of the crystal guava agro-industry supply chain, identify the risks that arise within the supply chain, and devise effective mitigation strategies to mitigate these risks. The informants in this research were three individuals who were experts in the company's supply chain. Vorst (2006) framework is implemented in this investigation to ascertain the supply chain's structure and mechanism. The SCOR model is employed to map supply chain activities in order to identify the risks that arise and develop effective mitigation methods. Subsequently, the HOR method and Pareto diagram are employed to classify the risks and any associated mitigation. The study's findings indicate that the company's supply chain comprises industrial entities, farmers, product retailers, and final consumers. 51 risk events, 51 risk agents, and 29 priority risk agents were acquired by HOR Model one. 12 priority mitigation strategies that require immediate implementation were obtained by HOR Model 2. Additionally, 20 mitigation strategy proposals were obtained.